2022
DOI: 10.3389/fphar.2022.878371
|View full text |Cite
|
Sign up to set email alerts
|

Tibetan Herbal Pain-Relieving Plaster for Chronic Musculoskeletal Pain Among Cancer Survivors: Study Protocol of a Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: Chronic pain is common and debilitating in cancer survivors. Tibetan herbal pain-relieving plaster is used as an external analgesic to treat musculoskeletal pain in China; however, its safety and efficacy have not been evaluated via clinical trials in cancer survivors. We designed this Phase II randomized, double-blind, placebo-controlled trial (ClinicalTrials.gov Identifier: NCT04916249) to assess the efficacy and safety of the pain-relieving plaster for temporary pain relief among cancer survivors with chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Practitioners of traditional Tibetan medicine (TTM), an influential part of Chinese herbal medicine, have constructed a whole theoretical, clinical medicine system based on empirical experience gained during the past few centuries [ 7 ]. TTM is now widely accepted in various Asian countries, and studies have shown that it has definite curative effects in preventing cancerous lesions and reducing adverse reactions after anticancer therapy [ 8 , 9 , 10 , 11 ]. Additionally, the complex mechanisms through which TTM therapy functions in various types of cancer have been elucidated using emerging network pharmacology-based methods [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Practitioners of traditional Tibetan medicine (TTM), an influential part of Chinese herbal medicine, have constructed a whole theoretical, clinical medicine system based on empirical experience gained during the past few centuries [ 7 ]. TTM is now widely accepted in various Asian countries, and studies have shown that it has definite curative effects in preventing cancerous lesions and reducing adverse reactions after anticancer therapy [ 8 , 9 , 10 , 11 ]. Additionally, the complex mechanisms through which TTM therapy functions in various types of cancer have been elucidated using emerging network pharmacology-based methods [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%